POWER QUALITY IN THE LOW-VOLTAGE AIR NETWORK (Spectrum Journal of Innovation, Reforms and Development, 2023)
Objective. One of the important criteria for evaluating electrical energy is the indicators that characterize the symmetry of this three-phase voltage system. In the analysis of these indicators, the peculiarities of the three-phase network, including the uneven operating modes, the diversity of consumers, the occurrence of power imbalances as a result of non-uniform distribution of phases, the resulting nonlinear distribution of voltage across phases, the possibility of equal distribution of single-phase consumers limited, as well as the diversity of power consumption, factors that negatively affect the neutral operating mode, the nonlinear nature of the power consumption, and other factors lead to factors that cause voltage symmetry of the three-phase network. Methods. There are several specific measures to bring the voltage symmetry of the three-phase network to the required level, which is based on the analysis of the calculated parameters, based on the current operating mode of the existing network, the condition of the elements in the connection scheme. This takes into account not only the normal operation of the three-phase network, but also the requirements of the normative operation of single-phase consumers. Due to this requirement, it is difficult to calculate and analyze the voltage symmetry of three-phase networks. This article refers to one of the measures aimed at eliminating voltage asymmetry, which is relevant in terms of complexity. One of the main reasons for the fact that the power quality indicators exceed the normative indicators is the significant additional active losses of electricity in the symmetrical parts of the reverse and zero-sequence currents passing through the elements of the power grid. Results. The purpose of the study was to analyze the quality and additional losses of electricity in 0.4 kV transmission lines (TP-503,504 and 518) in the Andijan region. Conclusion. Thus, the analysis showed that the operating mode of the tested power grid is symmetrical, in particular, requires the installation of asymmetrical devices to reduce additional losses and improve the quality of electricity.